A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge - Byrkjedal, Ingvar; Orlov, Alexei M. (Zootaxa, 2007)
Cottunculus tubulosus n.sp. is described from one specimen caught in the summer of 2004 in the Northeast Atlantic, at about 2000 m depth in the Mid Atlantic Ridge. The species is characterised by a slender body, a long head, large pointed cranial spines, large bony tubules along the lateral line, prominent dermal prickles along the back, dorsal and anal fins set far posterior, a short caudal peduncle, and no banded colour patterns. From morphological characters, the species seems closely related to the South African species C. spinosus.